Pendidikan Jender Bagi Calon Guru SD Dalam Rangka Penyiapannya Menjadi Agen Sosialisasi Jender di Sekolah Dalam Rangka Pendekonstruksian Nilai Jender Pada Anak Menuju Tatanan Kehidupan yang Egalitarian - Rr. Nanik Setyowati, ; Oksiana Jatiningsih, (Pelangi Ilmu, 2007)
ABSTRAK Teachers have important and strategic roles, especially for children who stay at elementary and low school level. On school ages, especially at elementary school, children are on important position on building their gender frame, because children are more easily built by older people. Therefore, learning experience anf teachers treatment to children are so importantly paid attention because not only teachers roles are as  so information and identification and imitation resources (Kagan and Lang, 1978:64), but also the reality that so many books used at schools are gender-bias. Unfortunately, teachers and learning aids are coluored by traditional gender value. In preparing children on living at changing society, it is important to build gender awareness and socialize egalitarian gender values. This is mainly very important to do to future kinder garten and elementary school teachers as the future gender socialization agents at school. Here, it is very important to conduct gender education at PGSD program where elementary school teachers are educated.